Pesan Dakwah dalam Iklan Deterjen dan Pewangi “Cosentrat Sahaja” - Royhaa Natul Firdaus (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract.This study aims to determine the message of da'wah contained in the detergent and fragrance advertisement "Cosenrat Sahaja" using Roland Bhartes' semiotic analysis. In several scenes contained in the detergent and fragrance advertisement "Cosentrat Sahaja" there are da'wah messages that we can find in everyday life. Advertising as a marketing tool through promotion is a communication process that aims to influence the interest of prospective buyers so that they are able to market their products in bulk. Da'wah is an activity to invite or call on goodness. And da'wah activities can be found in various works of art in the form of audio, visual, or audio visual. The value of the da'wah can be represented or described in an advertisement. Detergent and Fragrance Advertisement "Cosentrat Sahaja" is one of the advertising arts that tells about a family who uses detergent and fragrance products "Cosentrat Sahaja" when they are going to carry out daily life activities. described in the activities shown. So the researchers are interested in conducting this research in order to answer the problem: How is the content of the message of da'wah contained in the advertisement. This study uses a descriptive qualitative approach with a semiotic analysis method whose theory is put forward by Roland Barthes in the official YouTube account belonging to SAHAJAID. As a support, researchers also use secondary data referred to from journals, articles, and previous research. The results showed that, in the advertisement for detergent and fragrance "Cosenrat Sahaja", there was a message of Islamic da'wah and morality. Abstrak. Penelitian ini bertujuan untuk mengetahui pesan dakwah yang terkandung dalam iklan deterjen dan pewangi “Cosentrat Sahaja” dengan menggunakan analisis semiotika Roland Bhartes. Dalam beberapa scene yang terdapat dalam iklan deterjen dan pewangi “Cosentrat Sahaja” terdapat pesan dakwah yang dapat kita temukan dalam kehidupan sehari-hari. Iklan sebagai salah satu alat pemasaran melalui promosu merupakan proses komunikasi yang bertujuan mempengaruhi minat calon pembeli sehingga mampu memasarkan produknya secara massal. Dakwah merupakan kegiatan mengajak atau menyeru pada kebaikan. Dan kegiatan dakwah dapat ditemukan dalam berbagai karya seni baik berupa audio, visual, atau audio visual. Nilai dakwah tersebut dapat direpresentasikan atau digambarkan dalam sebuah iklan. Iklan Deterjen dan Pewangi “Cosentrat Sahaja” merupakan salah satu seni iklan yang mengisahkan tentang keluarga yang menggunakan produk deterjen dan pewangi “Cosentrat Sahaja” pada saat akan melakukan aktivitas kehidupan sehari-hari Dalam iklan deterjen dan pewangi “Cosentrat Sahaja” tersebut juga terdapat pesan dakwah yang tergambarkan dalam kegiatan-kegiatan yang ditampilkan. Maka peneliti tertarik untuk melakukan penelitian ini guna menjawab permasalahan: Bagaimana isi pesan dakwah yang ada dalam iklan tersebut. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis semiotika yang teorinya dikemukakan oleh Roland Barthes dalam akun YouTube resmi milik SAHAJAID. Sebagai penunjang, peneliti juga menggunakan data sekunder yang dirujuk dari jurnal, artikel, serta penelitian terdahulu. Hasil penelitian menunjukkan bahwa, dalam iklan deterjen dan pewangi “Cosentrat Sahaja”, terdapat pesan dakwah Syariah dan akhlak.